Intelligent muslim prayer counter with programmable interface controller (PIC) - Hassim, Hasniza (2014)
Praying five times a day is a pillar of Islam which is fulfilled by all Muslims. Every rule of prayer should be implemented so that prayer worked perfectly acceptable to God. However, when performing prayer, it is possible that we lose focus and this has been proven through studies Electroencephalography studies. Very often we pray, we are doubt about the number of units completed, especially during perform four raka’ah prayers. Intelligent Muslim Prayer Counter with PIC algorithm has been designed to solve this problem. The use of the PIC algorithm is also not just limited to this current product but it can also be used to improve future products. One existing design has been review to find the product weaknesses and the improvement needed. A project by Hassan Faouaz which entitled Muslim Prayer Counter has been reviewed to develop the new circuit and study the weaknesses for the improvement for this invention. The design is also focus on the suitability for all different size of user and the design of algorithm used to program the PIC chip. By using PIC algorithm, there are more improvement can be made in future based on further value added requirement request by user or manufacturer.